Mothering Children with Neurological Disability: Focus on Vhembe Rural Community South African - Christinah Sadiki Marubini; Obert Maguvhe Mbulaheni (Journal of Education, Society & Multiculturalism)
Mothering a child with a disability is by no means a small challenge, especially for mothers as often they tend to take a greater responsibility for the child. This article mainly aims to provide an understanding challenge encountered by mothers when mothering their children with neurological disability in a rural South African setting. The study used a phenomenological research design. Authors of this article purposefully recruited eight mothers of children with neurological disability between the ages of 39 and 55 in a rural South African Limpopo setting. Interpretive data analysis method was employed to provide valuable data on encountered by mothers of children with neurological disability. Data were collected using semi-structured interviews. Semi-structured face-to-face interviews were conducted, and the data results were thematically analysed on mothering children with neurological disabilities. The results show conform to grassroots realities. The findings revealed the following three themes and two sub-themes emerged: (1) health services (sub-themes: health services as an important aspect to mothers of children with ND; lack of adequate knowledge about disability and resources) (2) religious beliefs; and (3) the mother's reaction to neurological disability. Additionally, results have revealed mothering a child with a neurological disability triggered several changes in family dynamics. This study contributes to the experiences of individuals' understanding of the challenges of mothering children with neurological disabilities in a rural South African setting.